(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2025)
The construction sector has the potential to improve its sustainability through the application of circular economy principles, which primarily emphasize two cycles: replacing conventional materials with biological alternatives and enhancing the recycling of technical materials. This study aims to analyze the current facade design of the Engineering Center (EC) Building at Universitas Indonesia (UI) as an initial study to explore Alternative Design (AD) with a hybrid approach of biological and technical cycles. This study’s method mixes Building Circularity Calculation (BCC) and incorporates Material Passport (MP) and Material Flow Analysis (MFA). The study emphasized that utilizing mycelium brick (predominantly a biological material, comprising 63%) has outstanding potential to achieve building circularity implementation in the EC Building facade. The finding highlights a hybrid design strategy, incorporating a significant proportion of biological materials, could be a promising pathway for implementing building circularity in the EC Building. Biological materials are generally causing less environmental impact compared to technical materials, yet further mitigation strategies are required due to their shorter lifespan. To build based on these findings, exploring a wider range of building components and other possible variants of hybrid designs are recommended in future research.